Non-esterified fatty acid (AGNE) in serum of pregnant women, newborns and normal height men - Llerena, Luis (2015)
We performed a comparative study of the levels of non-esterified fatty acids (AGNE) under the following conditions: a) Basal and during the oral glucose tolerance (TOG) in 6 non-pregnant women and 10 pregnant women in the third quarter of Cerro native Pasco (4,300 m.) and 8 pregnant native third quarter of La Oroya (3,700 m.) vs. 15 non-pregnant women and 19 pregnant women in the third trimester, native of sea level. b) Basal in 20 non-pregnant women, 20 normal adult men and 11 infants vs. Cerro de Pasco 15 non-pregnant women, 15 normal adult men and 10 newborn sea level.